Expression and Purification of Tag-removed Human IL37 by Digestion on Beads in Escherichia coli - Wu, Daichao; Li, Guoqing; Ma, Yao; Liu, Jin; Li, Yukun; Wang, Juan; Bai, Junhui; Tan, Sijie; Li, Meixiang; Chen, Yongheng (Protein and Peptide Letters, 2018)
Background: Human Interleukin 37 (IL37), a unique anti-inflammatory cytokine of IL1 family member, plays critical roles in innate and adaptive immunity and inflammation. Objective: Preparation of high purity and tag-removed recombinant IL37 protein (rIL37) is critical for its clinical application. Method: In this study, we constructed an N-terminal cleavable GST-fused IL37 expression vector for recombinant expression. Results: Subsequent to transformation and optimization of the induction temperature, the soluble expression level of rIL37 was 306.5 mg/L of culture medium at 18 °C induction in Escherichia coli. Meanwhile, rIL37 was digested on beads by GST-HRV3C protease during GST affinity chromatography. After further purification, the purity of rIL37 was higher than 99 %. Finally, the antiinflammatory activity of tag-removed protein was verified by the results showing that rIL37 suppressed IL1β production in PBMCs. Conclusion: This work presents a protocol to produce high purity and tag-removed rIL37 with antiinflammatory activity, which provides the firm basis for advancing clinical application in human IL37-related inflammatory diseases.
Keywords: Escherichia coli